MEMPROGRAMKAN PENGENALAN AKUNTANSI SYARIAH BAGI USAHA MIKRO KECIL DAN MENENGAH DI DESA PURASEDA, KECAMATAN LEUWILIANG , KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Bayu Purnama Putra; Mohammad Algifari (SAHID EMPOWERMENT JOURNAL, 2022)
Micro, Small and Medium Enterprises or often referred to as MSMEs are very important for the government to pay attention to. MSMEs are businesses that are managed by small people with limited capital. MSMEs are part of the Indonesian economy. Therefore there should always be assistance for MSMEs. In community service activities carried out in Puraseda Village, Leuwiliang District, Bogor Regency from July to August 2021, MSMEs in the village were given an introduction to sharia accounting. This sharia accounting will strengthen MSMEs which have been carrying out Islamic economic and business activities in the sense of carrying out halal activities. MSMEs understand sharia accounting which makes MSME financial arrangements more tidy and clear.